The preferred learning Styles of Dhofar University students in the Sultanate of Oman (Journal Of Educational and Psychological Researches, 2024)
The current study aimed to investigated the preferred learning styles of University students. The data were collected from 554 students at Dhofar University. The students were enrolled on different programs of study across three Colleges. Namely, these colleges are the College of Arts and Applied Sciences (CAAS), the College of Commerce and Business Administration (CCBA) and the College of Engineering (CE). Our sample consisted of 303 female students and 251 male students. The researchers used Felder and Soloman index of learning styles to measure the participants’ preferred style of learning. The findings of this study shed light on the importance of understanding individual learning preferences and their influence on the overall learning experience. The results of the study revealed that students in Oman demonstrated varied preferences for different learning styles, including 'active' or 'reflective', 'sensing' or 'intuitive', 'visual' or 'verbal', and 'sequential' or 'global' learning. These preferences play a significant role in shaping how students process information, engage in learning activities, and ultimately achieve academic success